PENGARUH TERAPI FARMAKOLOGI DAN NON-FARMAKOLOGI TERHADAP PENURUNAN NYERI MENSTRUASI PADA MAHASISWI FAKULTAS FARMASI UNIVERSITAS BHAKTI KENCANA BANDUNG - Anggriani, Ani; Mulyani, Yani; Pratiwi, Lili Dinda (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2021)
Menstrual pain is a problem that women often complain about in their teens. Menstrual pain (dysmenorrhea) is pain before or during menstruation in the lower abdomen due to uterine cramps. The prevalence of dysmenorrhea in Indonesia is 54% primary dysmenorrhea and 9% secondary dysmenorrhea. Due to the severe pain that is felt during menstruation, 10% of teenage girls are absent from school and work for 3 days each month. This study aims to determine the effect of pharmacological & non-pharmacological therapy on reducing menstrual pain in adolescents. This research is an experimental research with one group pretest-post test design. The research sample used purposive sampling method, with a sample of 76 respondents. Data were analyzed using the Wilcoxon Signed Rank Test & chi-square test. The results showed that the Wilcoxon test with the results of Sig. 0.000<0.05, meaning that there is a difference in the intensity of menstrual pain before & after therapy. So it can be concluded that there is an effect of pharmacological and non-pharmacological therapy on decreasing the intensity of menstrual pain. For the relationship of non-pharmacological therapy Chi-Square test results have a value of Sig. 0.514>0.05, meaning that there is no significant relationship to the intensity of menstrual pain. For the relationship between pharmacological therapy, the results of Sig. 0.019<0.05, meaning that there is a significant relationship with the intensity of menstrual pain in adolescent girls at Bhakti Kencana University, Bandung.